2012
DOI: 10.3844/ajabssp.2012.50.55
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory Responses of the Asiatic Citrus Psyllid (<i>Diaphorina citri</i>) to Mineral Oil-Treated Mandarin Leaves

Abstract: Problem statement: Evidence of rejection or acceptance by phytophagous pests of citrus plants treated with mineral oils suggests that impacts of oils may be related to detection by olfactory and/or contact chemoreceptors of repellent oils or plant volatiles. Alternatively, the oils may mask or suppress attractant host plant volatiles. To date, no studies have reported that oils elicit an olfactory response in Diaphorina citri Kuwayama [Hemiptera: Psyllidae]. Therefore, we undertook two studies to determine how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(1 citation statement)
references
References 18 publications
(21 reference statements)
0
1
0
Order By: Relevance
“…Adult D. citri were strongly attracted to targets consisting of a combination of ultraviolet and yellow or green light. Other studies reported the role of constitutive plant volatiles in host plant selection by members of the Liviidae (Moran and Brown, 1973;Nehlin et al, 1994;Soroker et al, 2004;Cen et al, 2005;Nissinen et al, 2008;Rouseff et al, 2008;Patt and Setamou, 2010;Onagbola et al, 2011;Patt et al, 2011;Poerwanto et al, 2012;Robbins et al, 2012). Volatile stimuli associated with flushing shoots may play an important role in detection, location and evaluation of potential host plants by D. citri (Patt and Setamou, 2010;Sule et al, 2012) while other studies emphasized the limited role of volatile signals in this species (Lapointe et al, 2016).…”
Section: Introductionmentioning
confidence: 98%
“…Adult D. citri were strongly attracted to targets consisting of a combination of ultraviolet and yellow or green light. Other studies reported the role of constitutive plant volatiles in host plant selection by members of the Liviidae (Moran and Brown, 1973;Nehlin et al, 1994;Soroker et al, 2004;Cen et al, 2005;Nissinen et al, 2008;Rouseff et al, 2008;Patt and Setamou, 2010;Onagbola et al, 2011;Patt et al, 2011;Poerwanto et al, 2012;Robbins et al, 2012). Volatile stimuli associated with flushing shoots may play an important role in detection, location and evaluation of potential host plants by D. citri (Patt and Setamou, 2010;Sule et al, 2012) while other studies emphasized the limited role of volatile signals in this species (Lapointe et al, 2016).…”
Section: Introductionmentioning
confidence: 98%